The association between liver fibrosis scores and chronic kidney disease - Xiong, Shengjun; Wang, Pengbo; Yin, Shizhang; Deng, Wanshu; Zhao, Yuanhui; Li, Wenhang; Li, Zhao; Zhou, Ying; Yu, Shasha; Yang, Hongmei; Guo, Xiaofan; Sun, Yingxian (Frontiers in Medicine, 2023)
Purpose: To clarify the relationship between liver fibrosis scores (Fibrosis-4, BARD score, and BAAT score) and chronic kidney disease (CKD). Methods: We collected a range of data from 11,503 subjects (5326 males and 6177 females) in rural regions of Northeastern China. Three liver fibrosis scores (LFSs) including fibrosis-4 (FIB-4), BARD score, and BAAT score were adopted. Logistic regression analysis was used to calculate odds ratios and the 95% confidence interval. Subgroup analysis showed the association between LFSs and CKD under different stratification. Restricted cubic spline could further explore whether there is a linear relationship between LFSs and CKD. Finally, we used C-statistics, Net Reclassification Index (NRI) and Integrated Discrimination Improvement (IDI) to assess the effect of each LFS for CKD. Results: Through the baseline characteristics, we observed that LFSs were higher in the CKD population than non-CKD. The proportion of participants with CKD also increased with LFSs. In the multivariate logistic regression analysis, the ORs of CKD were 6.71 (4.45-10.13) in FIB-4, 1.88 (1.29-2.75) in the BAAT score, and 1.72 (1.28-2.31) in the BARD score by comparing the high level with the low level in each LFSs. Moreover, after adding LFSs to the original risk prediction model, which consisted of age, sex, drinking, smoking, diabetes, low-density lipoprotein cholesterol, total cholesterol, triglycerides, and mean waist circumference, we found the new models have higher C-statistics. Furthermore, Net Reclassification Index (NRI) and Integrated Discrimination Improvement (IDI) both indicate LFSs had a positive effect in the model. Conclusions: Our study showed that LFSs are associated with CKD among middle-aged populations in rural areas of northeastern China.